Development And Properties Of Resin Impregnated Microwave Dried Oil Palm Trunk Core Lumber - Amouzgar, Parisa (2011)
In this study the optimization of drying oil palm trunk core lumber (OPTCL) biomass using microwave radiation was reported. Optimizing of the drying conditions using microwave could avoid burning, shrinkage and increasing the permeability of OPT was aimed to develop a new value added material. Drying the core part of oil palm trunk using microwave was completed in this study for the first time. A set of experiments was designed by central composite design using response surface methodology (RSM) to statistically evaluate the findings and developed a model to predict drying prameters.